Circulating microRNAs for the prediction of metastasis in breast cancer patients diagnosed with early stage disease - Inns, Joseph; James, Victoria (Elsevier, 2015)
Breast cancer is the second most common malignancy diagnosed in women worldwide. The greatest cause of breast cancer mortality is development of metastasis. For many women metastasis is an early event in breast cancer which goes undetected until its presentation, thus there is an urgent need for the development of biomarkers to predict those patients at greatest risk. The expression of a group of small non-coding RNAs, termed microRNAs, has been shown to be altered in tumours. Furthermore, microRNAs identified as being highly expressed in breast cancer tumours can also be detected in the circulation. Circulating microRNAs are an emerging field of biomarker research which have the benefit of being able to be obtained non-invasively and analysed rapidly and relatively cheaply. Here the potential use of circulating miRNAs to detect metastasis in discussed and the current barriers to their progression to the clinic.